Weather in Texas : the essential handbook - Bomar, George W. (University of Texas Press, 2017)
Only in Texas could a snowstorm pelt the Panhandle at the very moment abrasive dust is scouring the Permian Basin while searing heat is wilting the Winter Garden region in the south. The state's large size and central location within North America subject it to a great variety of weather occurrences. Texas state meteorologist George W. Bomar has been observing Texas weather for nearly half a century, and in Weather in Texas, he provides the essential guide to all of the state's weather phenomena. Writing in lively layman's language, Bomar fully explains both how the weather works and how Texans can prepare for and stay safe during extreme weather events. He describes the forces that shape Texas weather from season to season, including the influence of tropical cyclones, frontal boundaries, El Niño, and the polar jet stream. Bomar puts specific weather events in historical context, using a ranking system to illustrate how recent droughts, snowstorms, hurricanes, flash floods, and tornadoes compare with those of previous generations. He also includes comprehensive tabulations of weather data for every area of Texas, quantifying what constitutes "normal" weather, as well as the extreme limits of variables such as low and high temperatures, rain days, snow accumulations, and earliest and latest freezes. With everything from the latest science on climate change and weather modification to dramatic stories about landmark weather events, Weather in Texas is a must-have reference for all Texans